Enhancing Phenolic Contents and Antioxidant Potentials of Antidesma thwaitesianum by Supercritical Carbon Dioxide Extraction. (21st April 2015) - Poontawee, Warut; Natakankitkul, Surapol; Wongmekiat, Orawan
Abstract : Supercritical fluid extraction (SFE) has increasingly gained attention as an alternative technique for extraction of natural products without leaving toxic residues in extracts. Antidesma thwaitesianum Muell. Arg. (Phyllanthaceae), or ma mao, has been reported to exhibit antioxidant health benefits due to its phenolic constituents. To determine whether SFE technique could impact on phenolic contents and associated antioxidant potentials, ripe fruits of Antidesma thwaitesianum (Phyllanthaceae) were extracted using supercritical carbon dioxide (SC-CO2 ) and conventional solvents (ethanol, water). The results showed that the SC-CO2 extract contained significantly higher yield, total phenolic, flavonoid, and proanthocyanidin contents than those obtained from ethanol and water. It also demonstrated the greatest antioxidant activities as assessed by ABTS radical cation decolorization, DPPH radical scavenging, and ferric reducing antioxidant power (FRAP) assays. Further analysis using high-performance liquid chromatography with diode array and mass spectrometry detectors (HPLC-DAD/MSD) revealed the presence of catechin as a major phenolic compound of Antidesma thwaitesianum (Phyllanthaceae), with the maximum amount detected in the SC-CO2 extract. These data indicate that SFE technology improves both quantity and quality of Antidesma thwaitesianum fruit extract. The findings added more reliability of using this technique to produce high added value products from this medicinal plant.